Analysis of the Influence of Sharia Monetary Policy on Economic Development in Indonesia - Rania Ningsih; Bilal Kautsar Setiabudi; Moh azfahani zain; Nasya Amelia Putri (Penerbit Hellow Pustaka, 2024)
The Islamic economic system is considered capable of contributing to the global economy, including in Indonesia. This article aims to analyze monetary policy in Indonesia from an Islamic economic perspective. In this research, researchers observe monetary policy instruments, namely open market operations, where in general, monetary targets are aimed at encouraging economic growth and stabilizing inflation. The methodology used is a literature study approach to three main journals and several national and international journal articles related to sharia monetary. The main finding of this research is that the development of sharia-based monetary policy in Indonesia is considered to have an important role in economic development in Indonesia.